(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the holistic approach to caring for patients with chronic respiratory conditions, emphasizing the multifaceted nature of nursing care in addressing physical, emotional, social, and spiritual needs. Chronic respiratory conditions, such as asthma, chronic obstructive pulmonary disease (COPD), and cystic fibrosis, significantly impact patients’ quality of life and require comprehensive management strategies. The bio-psycho-social-spiritual model serves as a framework for understanding and addressing the complex needs of these patients. Assessment and diagnosis involve a thorough evaluation of respiratory symptoms, psychosocial factors, and diagnostic tests. Collaborative care planning emphasizes interdisciplinary teamwork and patient involvement in setting goals. Management strategies encompass pharmacological and non-pharmacological interventions, with a focus on patient education and self-management. Promoting self-management and empowerment involves teaching self-monitoring techniques and facilitating lifestyle modifications. Psychosocial support and counseling are essential components of care, addressing patients’ emotional and psychological needs. Nurses play a central role in providing holistic care, fostering patient-centered approaches to enhance respiratory health outcomes.